2004
DOI: 10.1086/423962
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Dissemination in England of a Stable and Persistent Hepatitis B Virus Variant

Abstract: The finding of a single, genetically identical variant (over the 600 bp sequenced) occupying a large niche among the circulating viruses was unexpected. This finding has major implications for the use of DNA sequencing analysis in the investigation of chains of transmission. The study also highlights the need for better protection of at-risk groups through vaccination against HBV, a strategy that currently achieves poor coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
(30 reference statements)
0
25
0
Order By: Relevance
“…Nonetheless, although each of the three factors was shown to be independently associated with infection by cluster 1 strains, MSM activity is the behavioral risk factor identified that would account for the observed increase in the rate of transmission of these genetically close strains. Although locally circulating HBV strains may be expected to be genetically (20,21). As noted, rapid transmissions among acutely infected MSM in the Netherlands and Japan (25,26) were associated with genetically identical or closely related A2 strains.…”
Section: Genetic Analysis Of Hbv Wg Sequences Confirmed Significant Pmentioning
confidence: 85%
See 1 more Smart Citation
“…Nonetheless, although each of the three factors was shown to be independently associated with infection by cluster 1 strains, MSM activity is the behavioral risk factor identified that would account for the observed increase in the rate of transmission of these genetically close strains. Although locally circulating HBV strains may be expected to be genetically (20,21). As noted, rapid transmissions among acutely infected MSM in the Netherlands and Japan (25,26) were associated with genetically identical or closely related A2 strains.…”
Section: Genetic Analysis Of Hbv Wg Sequences Confirmed Significant Pmentioning
confidence: 85%
“…The high incidence of A2 in acute cases in the United States parallels other global reports. In Europe, the majority of incident HBV strains belong to A2 (19,20), with specific strains identified in English prisons (21), in outbreaks of nosocomial HBV transmissions in Germany (22) and Belgium (23), and among MSM in The Netherlands (24). In Japan, HBV A2 has been observed to be spreading not only within the MSM community (25) but also from there to the general population (26).…”
Section: Hbv Genetic Diversitymentioning
confidence: 99%
“…This has been reported in a large outbreak of HBV infection in the United Kingdom where two new variants of A and D genotypes have spread in large population groups through injecting drug use and heterosexual sex (Hallett et al, 2004;Andersson et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
“…A search of Medline and EMBASE databases from 1972 to the end of 2007 produced 946 citations, from which 18 articles describing 25 community-based HBV outbreaks in developed countries were identified [3]. The previously published community-based HBV outbreaks in the UK reported 3-119 cases [15][16][17][18][19][20]. Injecting drug use was reported to be the most common route of transmission in all these reported studies, except one report of three cases [16].…”
Section: Discussionmentioning
confidence: 99%
“…The previously published community-based HBV outbreaks in the UK reported 3-119 cases [15][16][17][18][19][20]. Injecting drug use was reported to be the most common route of transmission in all these reported studies, except one report of three cases [16]. In two studies of small outbreaks (both 14 cases) the route of transmission was not reported [16].…”
Section: Discussionmentioning
confidence: 99%